Photovoltaic Materials and Electronic Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Given the state-of-the-art in solar photovoltaic (PV) technology and favorable financing terms, it is clear that PV has already obtained grid parity in specific locations [1]. Advances in the next generation of photovoltaic materials and photovoltaic devices can further reduce costs to enable all of humanity to utilize sustainable and renewable solar power [2]. This Special Issue of Materials will cover such materials, including modeling, synthesis, and evaluation of new materials and their solar cells. Specifically, this Special Issue will focus on five material technologies for advanced solar cells: 1. New Concepts in PV Materials: Nanostructured materials, low-dimensional physics, multiple charge generation, up/down converters, thermophotovoltaics, low-cost III-V materials, bandgap engineering, hot-carrier effects, plasmonics, metamorphic materials, perovskite and related novel PV materials, novel light trapping, rectennas, quantum dots, carbon nanotubes, and graphene composites. 2. Organic PV Materials: Polymer, hybrid and dye sensitized solar cells, high performance contacts, and lifetime degradation and mechanisms. 3. Dye-Sensitized Solar Cells (DSSCs) Materials: Recent developments in dyes, working electrodes, technologies for device fabrications, and advances in new electrolytes. 4. Amorphous, Nanostructured, and Thin Film Silicon PV Materials: Microstructure characterization, light induced degradation (SWE), large area and high deposition rates, novel processing routes, light trapping, multi-layers, and multi-junction devices. 5. Passive Materials for all PV: Transparent conductive oxides (TCOs), encapsulation, connections, optics, glass, anti-reflection coatings (ARCs), alternative buffer layer materials, and contacts.